2018
DOI: 10.1177/0363546518773755
|View full text |Cite|
|
Sign up to set email alerts
|

A 2-Year Prospective Cohort Study of Overuse Running Injuries: The Runners and Injury Longitudinal Study (TRAILS)

Abstract: The results of this study indicate the following: (1) among recreational runners, women sustain injuries at a higher rate than men; (2) greater knee stiffness, more common in runners with higher body weights (≥80 kg), significantly increases the odds of sustaining an overuse running injury; and (3) contrary to several long-held beliefs, flexibility, arch height, quadriceps angle, rearfoot motion, lower extremity strength, weekly mileage, footwear, and previous injury are not significant etiologic factors acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
170
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 46 publications
13
170
2
3
Order By: Relevance
“…[37,40]. Strong evidence indicated no significant relationship between vertical impact peak and RRIs when comparing a group of injured and non-injured runners in three studies (ES = 0.03-0.35) [39,41,42]. However, using post hoc analysis of their data, Davis et al [42] reported higher vertical impact peak in female runners developing any RRI when comparing runners who required medical attention with runners who had never sustained an injury before (ES = 0.97) (limited evidence).…”
Section: Kinematicsmentioning
confidence: 95%
See 2 more Smart Citations
“…[37,40]. Strong evidence indicated no significant relationship between vertical impact peak and RRIs when comparing a group of injured and non-injured runners in three studies (ES = 0.03-0.35) [39,41,42]. However, using post hoc analysis of their data, Davis et al [42] reported higher vertical impact peak in female runners developing any RRI when comparing runners who required medical attention with runners who had never sustained an injury before (ES = 0.97) (limited evidence).…”
Section: Kinematicsmentioning
confidence: 95%
“…Inconsistent evidence was found for peak knee flexion in relation to RRIs in two studies. Specifically, very limited evidence indicated smaller peak knee flexion in a mixed-sex population of recreational runners developing Achilles tendinopathy (ES = 0.70) [38], while limited evidence indicated no significant association between peak knee flexion and RRI risk in a mixed-sex population of recreational runners (ES = 0.02) [39].…”
Section: Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. different sports-activities [21] and they have increased passive lower leg stiffness compared to XX counterparts [22] that might predispose to overuse injuries, especially in amateur endurance runners [23]. The most consistent finding has been the positive association between the XX genotype and ankle injuries [24][25][26] that suggests a negative impact of the XX genotype on joint and ligament injuries.…”
Section: Introductionmentioning
confidence: 98%
“…Running is an accessible and increasingly popular form of physical activity that is associated with reduced mortality (1)(2)(3)(4). However, there is a high incidence of injury amongst runners (5,6) with two-thirds of recreational runners reportedly sustaining an injury over a two-year period (6). Bone stress injuries are one of the more problematic injuries due in part to their lengthy recovery time and the most severe of thesestress fractureshave been reported to comprise up to 30% of running-related injuries (7).…”
Section: Introductionmentioning
confidence: 99%